Simulating drug penetration during hyperthermic intraperitoneal chemotherapy - Daan R. Löke; Roxan F. C. P. A. Helderman; Nicolaas A. P. Franken; Arlene L. Oei; Pieter J. Tanis; Johannes Crezee; H. Petra Kok (Taylor & Francis Group, 2021)
Hyperthermic intraperitoneal chemotherapy (HIPEC) is administered to treat residual microscopic disease after debulking cytoreductive surgery. During HIPEC, a limited number of catheters are used to administer and drain fluid containing chemotherapy (41-43 °C), yielding heterogeneities in the peritoneum. Large heterogeneities may lead to undertreated areas, increasing the risk of recurrences. Aiming at intra-abdominal homogeneity is therefore essential to fully exploit the potential of HIPEC. More insight is needed into the extent of the heterogeneities during treatments and assess their effects on the efficacy of HIPEC. To that end we developed a computational model containing embedded tumor nodules in an environment mimicking peritoneal conditions. Tumor- and treatment-specific parameters affecting drug delivery like tumor size, tumor shape, velocity, temperature and dose were assessed using three-dimensional computational fluid dynamics (CFD) to demonstrate their effect on the drug distribution and accumulation in nodules. Clonogenic assays performed on RKO colorectal cell lines yielded the temperature-dependent IC50 values of cisplatin (19.5-6.8 micromolar for 37-43 °C), used to compare drug distributions in our computational models. Our models underlined that large nodules are more difficult to treat and that temperature and velocity are the most important factors to control the drug delivery. Moderate flow velocities, between 0.01 and 1 m/s, are optimal for the delivery of cisplatin. Furthermore, higher temperatures and higher doses increased the effective penetration depth with 69% and 54%, respectively. We plan to extend the software developed for this study toward patient-specific treatment planning software, capable of mapping and assist in reducing heterogeneous flow patterns.